Kaunseling Kelompok Terapi Kognitif dalam Pengurusan Stres dalam kalangan Polis - Wan Anor Wan Sulaiman; Wan Nurfatini Wan Anor; Adi Fahrudin; Mohd Dahlan A. Malek (Asian Social Work Journal, 2018)
This article was written to discuss the use of cognitive therapy group counseling method in stress management among police personnel in Malaysia. It also discusses what police stress scenarios, stress factors, stress effects experienced by policemen in their work and lifestyle, and how existing programs have been done to reduce police stress. The results of this paper can give an idea and suggestion to the Royal Malaysian Police (PDRM) in intervention using cognitive counseling group interventions as a method that can be applied to high-stress police personnel in particular and who experience moderate stress.